Conversation Analysis and Ethnomethodology: the Centrality of Interaction - Halkowski, Timothy (Sage., 2010)
The paper summarizes the theoretical and methodological principles of Ethnomethodology and Conversation Analysis, two approaches which focus on the understanding of social action as it is produced by participants themselves. Particularly, the authors discuss the strengths and potentials of the two approaches in highlighting features of the communication between patients and health providers. The attention to the temporal and the collaborative character of talk is discussed as unique to Ethnomethodology and Conversation Analysis and considered as powerful way to understand how participants organize their actions and activities in the consultation. Finally the authors hint to the implications of the conversation analytic study of healthcare interactions for medical practice.
Keywords: Conversation analysis, ethnomethodology, interaction, communication, theory, research methods, temporality social action, healthcare interaction